al-ʿalāqah bayna fahm al-naḥw wa mahārāt al-qirāʾah li-ṭullāb al-ṣaff al-thāmin fī al-madrasah al-mutawassiṭah al-islāmiyyah al-ahliyyah "Miftāḥ al-ʿUlūm" Jārāk Kulon Jombang Jāwī al-Sharqiyyah - Nia Fatonah; Lailatul Qomariyah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
This article examines the relationship between nahwu science and reading skills in 8th grade students of Mt's Miftahul Ulum Jarak Kulon Jombang. This study aims to 1) know the understanding of science Nahwu 8th grade students MTs Miftahul Ulum Kulon Distance, 2) know the reading skills of 8th grade students Mt's Mifahul Ulum Jarak Kulon Distance, 3) know the relationship between science nahwu and reading skills in 8th grade students Mt's Miftahul Ulum Kulon distance. This study uses quantitative methods with data collection techniques from tests, interviews and documentation. The analysis technique used is Pearson product moment correlation. The results showed that 1) understanding of 8th grade students MTs Miftahul Ulum Kulon distance is included in the category of good enough with an average value of 74/21, 2) reading skills of 8th grade students MTs Miftahul Ulum jarak Kulon is included in the category of good enough with an average value of 75.34, 3) there is a relationship between nahwu science and reading there is a relationship between nahwu science and reading skills with a correlation value of 0.803 which means that the relationship between the two is very strong and the correlation coefficient value shows +1 which means it has a positive and comparable relationship.